2006
DOI: 10.1002/app.23337
|View full text |Cite
|
Sign up to set email alerts
|

Solution and solid‐state blend compatibility of poly(vinyl alcohol) and poly(methyl methacrylate)

Abstract: ABSTRACT:The blend miscibility of poly(vinyl alcohol) and poly(methyl methacrylate) in N,NЈ-dimethylformamide solution was investigated by viscosity, density, ultrasonic velocity, refractive index, and UV and fluorescence spectra studies. Differential scanning calorimetry and scanning electron microscopy were used to confirm the blend miscibility in the solid state. Blends were compatible when the concentration of poly(vinyl alcohol) was greater than 60 wt %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
7
11
0
Order By: Relevance
“…Moreover the absorption bands of PVA are all quite broad and severally overlapped in the 600–800 cm −1 region. The spectrum of PVA seems to be consistent with that previously reported in the literature …”
Section: Resultssupporting
confidence: 91%
“…Moreover the absorption bands of PVA are all quite broad and severally overlapped in the 600–800 cm −1 region. The spectrum of PVA seems to be consistent with that previously reported in the literature …”
Section: Resultssupporting
confidence: 91%
“…Such a difference between polymer–polymer interactions and blend–solvent interactions suggested the compatible nature of the blends in the studied range. Similar kinds of conclusions have also been reported by Aminabhavi and coworkers27 in the case of PMMA/polyvinyl alcohol blends in dimethyl formamide.…”
Section: Resultssupporting
confidence: 89%
“…[12,13] One of the hot and also controversial topics about this blend is their miscibility. [14][15][16][17][18][19][20] Strong evidence from some accurate measurements has shown that CS/PVA blend is not fully miscible at molecular level. The miscibility between CS and PVA in the blend was observed to depend on the preparation processing and the relative content of CS and PVA components.…”
Section: Introductionmentioning
confidence: 99%